2021
DOI: 10.3390/foods10112551
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gluten-Free Muffins with β-Glucan and Pomegranate Powder Using Response Surface Methodology

Abstract: More consumers are being diagnosed with celiac disease or diseases in which wheat products should be avoided. For this reason, it is important to increase the range of gluten-free products available. In this study, it was decided to optimize the technology for the creation of a muffin with β-glucan (BG) and pomegranate (PG), while establishing water share (WT), using the response surface methodology. It was shown that β-glucan and water had the most significant influence on specific volume and moisture (p ≤ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…The pomegranate seed powder and black carrot fiber addition had a negative impact on the reduction of the SV of the muffins as reported by Kurek et al 47 . and Singh et al ., 48 respectively.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The pomegranate seed powder and black carrot fiber addition had a negative impact on the reduction of the SV of the muffins as reported by Kurek et al 47 . and Singh et al ., 48 respectively.…”
Section: Resultssupporting
confidence: 53%
“…These results are in agreement with the results reported by Hussain et al 39 It has been reported that the increase in the dietary fibre content of muffins increased the density and reduced the SV because of the lower volume of air cells. 46 The pomegranate seed powder and black carrot fiber addition had a negative impact on the reduction of the SV of the muffins as reported by Kurek et al 47 and Singh et al, 48 respectively. The presence of insoluble fiber in PPP leads to increases in the frequency of the collapse of the muffin batter structure, and also prevents carbon dioxide gas bubbles, which is responsible for SV.…”
Section: Physical Properties Of Muffinmentioning
confidence: 69%
“…The measurement results are expressed following the system of the International Commission on Lighting (Comission Internationale de L'Eclarige) in the CIELab color space. The following parameters were determined and tested: L* (L = 0 (black), L = 100 (white)), a* (−a = green, +a = red), and b* (−b = blue, +b = yellow) [29]. Determinations were made in triplicate immediately after production.…”
Section: Color Measurementmentioning
confidence: 99%
“…Recent research developed a vegan muffin using the powdered cooking water of yellow soybeans instead of egg whites [ 6 ]. The quality of muffins can be easily upgraded to fulfill specific dietary requirements using fruit-based functional ingredients that can enhance muffin properties [ 7 , 8 , 9 ]. Changing the traditional composition of batter may change the sensory properties and consumer acceptance of muffins regarding color, texture, and flavor [ 10 ].…”
Section: Introductionmentioning
confidence: 99%